Evaluation of the proliferation of dedifferentiated cells of yellow bell pepper (Capsicum annuum cv. Pimentão amarelo). - SANTOS, M. R. A. dos (2017)
Capsicum annuum is notable for its secondary metabolites, which can be of great interest for use in agriculture as alternatives to agrochemicals. Cell suspensions have been used for in vitro largescale production of secondary metabolites. The aim of this study was to dedifferentiate leaf cells of Capsicum annuum cv. Pimentão Amarelo (yellow bell pepper) into calluses, and to study their growth pattern, focusing on the deceleration phase, when they can be subcultured to establish cell suspensions. Leaf explants were inoculated on MS medium supplemented with the growth regulators 2,4-D (0, 4.52, 9.05 and 18.10 µM) and BA (0, 4.44, 8.88 and 17.76 µM) in factorial combinations. Callus formation was evaluated weekly for 42 days, by assessing the number of callus induced per treatment and the weight of the explants. The culture medium supplemented with 4.52 µM 2,4-D and 4.44 µM BA resulted in the highest callus induction and weight of callus. For the identification of the growth curve the explants were submitted to this combination and in the subsequent 42 days, every seven days, the weight of the calluses was periodically measured. The growth curve has a sigmoid pattern and the deceleration phase begins 21 days after inoculation.